The Application of Factorial Design in Enhancing Soil Fertility Through Compost - Tatchanamurthy, Tarschny; Mohd Asrah, Norhaidah (Journal of Sustainable Natural Resources, 2024)
Nowadays, agriculture is practiced with high amounts of chemical fertilizers. Unfortunately, the overuse of chemical fertilizers resulted in a decrease in crop production and soil fertility. Organic fertilizer which is a low-cost and sustainable plant nutrition supply complements chemical fertilizers because it provides many benefits to soil fertility. There are three objectives in this study. Firstly, is to demonstrate optimal settings of the composts and the amount of water that will maximize the soil fertility using the method of 32 factorial design. The second objective is to study the effects of the composts and the amount of water on soil fertility by calculating the plant growth rate using the analysis of variance (ANOVA). The last objective is to compare the compost and the amount of water that increases the soil fertility by analysing the plant growth rate by using the main effects and interaction. Using 32 factorial designs with randomized complete blocks, 27 jasmine plants are randomly grouped into three different places which are the blocks. The compost used is dried leaves, orange, and banana peels. The height of the plants is measured at each pot and its plant growth rate is calculated for 30 days. It is then summed for each factor combination at each block. From this study, it is concluded that greater plant growth is attained which means soil fertility is maximized by the dried leaves with one cup of water followed by the orange peel with three cups of water and the banana peel with two cups of water. The results can be improved by taking the measurements for more than 30 days with the addition of composts and locations for the blockings.